A prodrug hydrogel with tumor microenvironment and near-infrared light dual-responsive action for synergistic cancer immunotherapy. (1st September 2022) - Ding, Mengbin; Fan, Yongliang; Lv, Yicheng; Liu, Jiansheng; Yu, Ningyue; Kong, Deping; Sun, Haitao; Li, Jingchao
Abstract: Immunotherapy has been used for cancer treatment, while it faces the common dilemmas of low therapeutic efficacy and serious immunotoxicity. In this study, we report the construction of a tumor microenvironment and near-infrared (NIR) light dual-responsive prodrug hydrogel for cancer synergistic immunotherapy in a more effective and safe manner. Such prodrug hydrogels were in-situ formed via calcium-induced gelation of alginate solution containing protoporphyrin IX (PpIX)‐modified iron oxide (Fe3 O4 ) nanoparticles and programmed death ligand 1 antibody (aPD-L1) prodrug nanoparticles crosslinked by reactive oxygen species (ROS)-responsive linkers. PpIX served as a photosensitizer to produce singlet oxygen ( 1 O2 ) under NIR laser irradiation for photodynamic therapy (PDT), and Fe3 O4 nanoparticles mediated chemodynamic therapy (CDT) to generate hydroxyl radical (·OH) via Fenton reaction in the tumor microenvironment. In view of the cumulative actions of PDT and CDT, amplified ROS was generated to not only induce immunogenic cell death (ICD), but also destroy ROS-responsive linkers to achieve on-demand release of aPD-L1 from prodrug nanoparticles. Boosted antitumor immunity was elicited in tumor-bearing mice due to the aPD-L1-mediated immune checkpoint blocking. As a result, the prodrug hydrogel-based synergistic immunotherapy could almost treat bilateral tumors and prevent lung and liver metastasis using 4T1 tumor mouse models. This study thus offers a dual-responsive prodrug hydrogel platform for precision cancer immunotherapy. Statement of significance: Via calcium-induced gelation of alginate, we constructed a prodrug hydrogel with tumor microenvironment and near-infrared light dual-responsive action for synergistic cancer immunotherapy. Such hydrogels can achieve on-demand release of aPD-L1 upon photoactivation in the tumor microenvironment. Through mediating photodynamic and chemodynamic therapy, the prodrug hydrogels can induce enhanced immunogenic cell death and synergistically improve the efficacy of aPD-L1-mediated immune checkpoint blocking. The prodrug hydrogel-based synergistic therapy almost deracinates the primary and distant tumors, and prevents lung and liver metastasis in tumor mouse models. Graphical abstract: Image, graphical abstract